2021
DOI: 10.3390/biology10100966
|View full text |Cite
|
Sign up to set email alerts
|

The Possible Role of Microbial Proteases in Facilitating SARS-CoV-2 Brain Invasion

Abstract: SARS-CoV-2 has been shown to display proclivity towards organs bearing angiotensin-converting enzyme (ACE2) expression cells. Of interest herein is the ability of the virus to exhibit neurotropism. However, there is limited information on how this virus invades the brain. With this contribution, we explore how, in the context of a microbial co-infection using a cryptococcal co-infection as a model, SARS-CoV-2 could reach the brain. We theorise that the secretion of proteases by disseminated fungal cells might … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 105 publications
(113 reference statements)
0
6
0
Order By: Relevance
“…Both HIV and SARS-CoV-2 can activate the NLRP3 in ammasome, precipitating immune imbalances through in ammasome activation 12 . Research has indicated that the novel coronavirus may instigate a cytokine storm, targeting endothelial cells and compromising the blood-brain barrier, consequently elevating the risk of central nervous system infections 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Both HIV and SARS-CoV-2 can activate the NLRP3 in ammasome, precipitating immune imbalances through in ammasome activation 12 . Research has indicated that the novel coronavirus may instigate a cytokine storm, targeting endothelial cells and compromising the blood-brain barrier, consequently elevating the risk of central nervous system infections 13 .…”
Section: Discussionmentioning
confidence: 99%
“…And that, any mutation to this amino acid sequence would impair furin hydrolysis. From the docking data, we established that furin protease and A. fumigatus alkaline protease 1 belong to the same family, thus would use common binding sites and have similar mechanistic features, i.e., defined by the nature of the nucleophilic amino acid in the active site [ 18 , 34 ]. Therefore, it is reasonable to foresee A. fumigatus alkaline protease 1 (serine-based) catalysing the SARS-CoV-2 spike protein similarly to furin protease.…”
Section: Discussionmentioning
confidence: 99%
“…For Cryptococcus neoformans —an encapsulated fungus responsible for pneumonia and meningitis in immunocompromised individuals—the activity of serine protease, as well as secreted metalloprotease Mpr1, was demonstrated as being pivotal for interactions with microvascular endothelial cells and the disruption of the blood–brain barrier, facilitating subsequent fungal traversal to the central nervous system [ 42 , 43 ]. Moreover, Mjokane et al [ 44 , 45 ] speculated recently that the activity of uncharacterized serine protease from C. neoformans may activate the SARS-CoV-2 spike (S) protein, with consequent membrane fusion and the endocytosis of virial particles by host cells, thus facilitating the development of the coronavirus disease COVID-19 in patients affected with concomitant fungal infection [ 44 , 45 ].…”
Section: Involvement In Binding Adhesion Self-aggregation and Biofilm...mentioning
confidence: 99%